Planejamento, instrumentos e resultados: Avaliaç\~ao da compatibilidade de políticas para o desenvolvimento do Nordeste - Constantino Cronemberger Mendes; Aristides Monteiro Neto (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This study aims to review some of the recent approaches to the regional problem in Brazil regarding the Northeast region. The focus of the analysis is more on the instruments predicted than on the diagnostics provided. In general, regional development policies take place through public and/or private mechanisms that are able to generate effective results in terms of output, employment and income. The challenge lies on identifying the 'means' that are most effective in the crucial phases of strategic planning: diagnostics, instruments design and goals setting. Our main goal is to make planning and budget compatible - one can spend more (priorities) or less (where waste is identified), while maintaining a balanced budget, coordinated instruments and the territorial-sectoral focus. Therefore, we need to revisit some important subjects: the way public decisions are made (social choice), how the budget is fixed, how the revenues are shared, how the mechanisms and instruments of regional policies are established, and if they are (or are not) compatible with the solution of fundamental problems and with relevant goals.
Keywords: O18; O21; H50; 330; Regionalplanung; Brasilien (Nordost)